2021
DOI: 10.3390/foods10071575
|View full text |Cite
|
Sign up to set email alerts
|

Chicken Authentication and Discrimination via Live Weight, Body Size, Carcass Traits, and Breast Muscle Fat Content Clustering as Affected by Breed and Sex Varieties in Malaysia

Abstract: Nowadays, the high demand for village chickens in Malaysia leads to the fraudulent substitution of indigenous chickens with other cheaper counterparts. Discriminating different chicken breeds based on their phenotypic characteristics is one strategy to avoid chicken adulteration. The main objective of this study was to authenticate and group dominant chicken breeds in Malaysia, including commercial chickens (Cobb, Hubbard, DeKalb) and cross-bred village chickens (Ayam Kampung, Akar Putra). The further discrimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 44 publications
(69 reference statements)
0
13
0
Order By: Relevance
“…Overall, carcass characteristics showed moderate variability (<25%), except AFW which had a CV of 92.11% among birds. In this regard, Nematbakhsh et al (2021) found that the variation in body fat content in broilers can be explained by breed, slaughter age and maturity stage of the birds. Internal fat is considered to be the most variable body component in farm animals (Bautista-Díaz et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, carcass characteristics showed moderate variability (<25%), except AFW which had a CV of 92.11% among birds. In this regard, Nematbakhsh et al (2021) found that the variation in body fat content in broilers can be explained by breed, slaughter age and maturity stage of the birds. Internal fat is considered to be the most variable body component in farm animals (Bautista-Díaz et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Previously, Juárez-Caratachea (2004) reported higher percentages of hot and cold dressing (78.94 and 75.91%, respectively), which were related to the higher slaughter body weigh to the native guajolotes used in that study (7.93 ± 0.69 kg). In poultry production, the dressing percentage is an important criterion for the evaluation of slaughter value of the carcass (Mueller et al, 2018;Nematbakhsh et al, 2021). Overall, carcass characteristics showed moderate variability (<25%), except AFW which had a CV of 92.11% among birds.…”
Section: Resultsmentioning
confidence: 99%
“…The above indicates that dietary MC supplementation could improve the meat quality by decreasing the pH and drop losses. What's more, the main target of commercial broiler chicken production is achieving high-yield and high-quality muscles, especially breast muscle, which is considered the most valuable piece of the chicken carcass and greatly affected by the breed ( 36 ). In the present study, dietary MC supplementation had no significant influences on the carcass trait.…”
Section: Discussionmentioning
confidence: 99%
“…Frontiers in Genetics frontiersin.org reported that genetic selection geared towards improvement in production traits could have an effect on the growth performance of the birds (Nematbakhsh et al, 2021). Both FUNAAB Alpha and Noiler have been genetically selected for improved dual-purpose (meat and eggs) performance in flocks owned by rural and peri-urban households.…”
Section: Figurementioning
confidence: 99%